Pengaruh Project Based Learning Melalui Kegiatan Daur Ulang Terhadap Kreativitas Anak Usia 5-6 Tahun - Asa Utami Sallewatang; Syamsuardi; Fitriani Dzulfadhilah; Angri Lismayani (Jurnal Kajian Anak (J-Sanak), 2025)
The development of creativity in children is often neglected due to monotonous learning. Therefore, the application of varied learning models in early childhood education such as project-based learning, is very important to support the development of creative and innovative thinking skills. This pseudo-experimental study was conducted to review how the application of project-based learning through recycling activities affects the creativity of children aged 5-6 years at TK Khalifah Makassar 3. The sample in this study was 30 children with 15 children as the experimental group and 15 children as the control group. Data collection techniques using observation, tests and documentation. The data analysis technique used was descriptive statistical analysis and nonparametric statistical analysis using the Wilcoxon Sign Rank Test. The observation results showed that children's creativity in the experimental group that applied project-based learning through recycling activities was higher than the control group. This increase is supported by the average pre-test score of the experimental group of 13.67 which increased to 23.67 in the post-test. Data analysis of significance with a value of Sig. (2-tailed) = 0.001 <0.05 indicates that H1 is accepted and H0 is rejected. This means that there is a significant difference in children's creativity in the experimental group before and after the project-based learning treatment through recycling activities, which indicates an increase in creativity. Therefore, the findings of this study conclude that the application of project-based learning through recycling activities has a positive effect on the creativity of children aged 5-6 years.